Language Dominance in Patients With Malformations of Cortical Development and Epilepsy - Kuchukhidze, Giorgi; Siedentopf, Christian; Unterberger, Iris; Koppelstaetter, Florian; Kronbichler, Martin; Zamarian, Laura; Haberlandt, Edda; Ischebeck, Anja; Delazer, Margarete; Felber, Stephan; Trinka, Eugen (Frontiers in Neurology, 2019)
Objective: Language function may be reorganized in patients with malformations of cortical development (MCD). This prospective cohort study aimed assessing language dominance in a large group of patients with MCD and epilepsy by use of functional MRI (fMRI). Methods: Sixty-eight patients (40 women) aged 10 - 73 years (median 28.0; interquartile range 22-41) with MCD and epilepsy underwent 1.5 Tesla MRI and fMRI (word generation task). Single-subject image analysis was performed with statistical parametric mapping (SPM12). Language lateralization indices (LIs) were defined for statistically significantly activated voxels in Broca's and Wernicke's areas using the formula: LI = (VL -VR)/(VL + VR) x100, where VL and VR were sets of activated voxels on the left and on the right respectively. Language laterality was considered typical if LI was between +20 and +100 or atypical if LI was between +19 and -100. Results: FMRI signal was elicited in 55/68 (81%) patients. In 18/55 (33%) patients, language dominance was typical and in 37/55 (67%) - atypical (in 68% – right hemispheric; in 32% – bilateral). There was a tendency of occurrence of an atypical language dominance in left-handers and in patients with left-hemispheric and bilateral MCD vs. right-hemispheric MCD as well as in those with left-hemispheric and bilateral vs. right-hemispheric seizure foci. Language dominance was not influenced by other electro-clinical and imaging features. Conclusions: In this prospective study on a large group of patients with MCD and epilepsy, about two-thirds had atypical language dominance. These results may contribute to assessing risks of post-surgical language deficits and could assist in planning of "cortical mapping" with intracranial electrodes in patients who undergo pre-surgical assessment.